Non-precious metal hydrogenation catalysts, their preparation methods and applications, selective hydrogenation of butadiene and 1-butene isomerization methods

By loading modified metal oxides and Cu and other components onto alumina and BEA molecular sieves, the problems of insufficient activity and poor resistance to sulfur compounds of non-precious metal catalysts were solved, and efficient hydrogenation of butadiene and isomerization of 1-butene were achieved.

CN116920927BActive Publication Date: 2025-11-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210377067.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-11
Publication Date
2025-11-14
Estimated Expiration
2042-04-11

AI Technical Summary

Technical Problem

Existing non-precious metal catalysts have insufficient performance in the selective hydrogenation of butadiene and the isomerization of 1-butene, and their tolerance to sulfur-containing compounds is poor, making it difficult to meet industrial needs.

Method used

Using alumina, molecular sieves with BEA structure, and modified metal oxides (such as titanium oxide, zirconium oxide, and cerium oxide) as supports, active metal Cu and other metal components (such as Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca, and W) are loaded onto the catalyst to form a uniformly dispersed non-precious metal hydrogenation catalyst through a specific preparation method.

Benefits of technology

It improves the catalyst's activity and resistance to impurities, especially its adaptability to sulfur-containing compounds, enhances the selectivity of butadiene hydrogenation and 1-butene isomerization, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116920927B_ABST
    Figure CN116920927B_ABST
Patent Text Reader

Abstract

This invention relates to the technical field of catalyst preparation, and discloses a non-precious metal hydrogenation catalyst, its preparation method and application, and a method for selective hydrogenation of butadiene and 1-butene isomerization. The catalyst comprises an active metal and a support, wherein the support comprises alumina, a molecular sieve with a BEA structure, and a modified metal oxide, wherein the modified metal oxide is at least one selected from titanium oxide, zirconium oxide, and cerium oxide; wherein the modified metal oxide has η < 0.3 and θ ≥ 50; wherein the active metal comprises Cu and optionally other metal components; wherein the other metal components are at least one selected from Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca, and W. This catalyst exhibits catalytic activity close to that of precious metal catalysts, significantly reducing catalyst costs. Furthermore, this catalyst also possesses extremely high 1-butene isomerization and desulfurization activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of catalyst preparation, specifically to a non-precious metal hydrogenation catalyst and its preparation method and application, as well as a method for selective hydrogenation of butadiene and isomerization of 1-butene. Background Technology

[0002] In the petrochemical industry, naphtha steam cracking produces abundant C4 olefins. Further processing of C4 olefins yields a series of products, including alkylated gasoline, methyl tert-butyl ether, blended gasoline, oligomeric gasoline, and tert-butanol. These can be added as clean blending agents in gasoline. Low carbon emissions, energy saving, and environmental protection are the biggest characteristics of C4 deep processing. In recent years, my country's refining and ethylene production capacity has been continuously increasing, and the MTO process has also seen significant improvements, promoting the continuous growth of total C4 production. With the increasing abundance of raw materials, the C4 deep processing industry has continued to develop and expand. However, these C4 olefins often contain small amounts of dienes or alkynes. In downstream olefin polymerization, dienes or alkynes are often more easily adsorbed onto the surface of the polymerization catalyst than monoolefins, leading to catalyst poisoning and inactivation. Therefore, the selective hydrogenation of dienes to generate monoolefins is often used to solve this problem.

[0003] Due to its high octane number, low vapor pressure, and good solubility in gasoline fraction hydrocarbons, methyl tert-butyl ether (MTBE) has seen rapid production growth in recent years. In the effluent (post-ether C4) of MTBE etherification units, after separating methanol and ether, the n-olefin content can reach 40-100% by weight. Currently, a large amount of post-ether n-butene resources are mainly burned as liquefied petroleum gas, thus necessitating the search for new applications. On the other hand, the continuous expansion of MTBE plants means that the isobutene production obtained from traditional petroleum catalytic cracking and thermal processing is far from meeting production needs. Therefore, skeletal isomerization of post-ether n-butene-rich materials to produce isobutene can achieve the goal of increasing isobutene production and is an effective way to reuse n-butene.

[0004] Furthermore, the rapid development of the automotive industry in recent years has led to an increasing demand for fuel, making isooctane production, a high-quality additive for gasoline, a focus of widespread attention. Currently, isooctane production feedstocks are mostly derived from mixed C4 hydrocarbons in refineries. This process uses concentrated sulfuric acid as a catalyst. However, butadiene in the feedstock reacts with concentrated sulfuric acid to form soluble sulfate esters, thus affecting the catalytic effect of the concentrated sulfuric acid. Currently, industrial processes often use extractive distillation to remove butadiene from C4 hydrocarbons, but it is difficult to reduce it below 10 ppm. Moreover, research has found that selective hydrogenation of butadiene can effectively reduce the butadiene concentration in C4 hydrocarbons, which is of great significance for the production of industrial alkylated oils. Therefore, there is an urgent need to develop a highly efficient catalyst-catalyzed method for the selective hydrogenation of 1,3-butadiene.

[0005] Catalysts for the selective hydrogenation of unsaturated hydrocarbons are mainly noble metals such as Au, Pd, and Pt. Although noble metals have high dissociation activation capabilities for hydrogen and exhibit very high activity in the selective hydrogenation of unsaturated hydrocarbons, their limited natural resources and high prices restrict their long-term development in the field of catalysis. During the preparation and practical application of noble metal catalysts, metal particles are prone to agglomeration, leading to a reduction in the contact area between the reactants and the active metal centers, thus decreasing catalyst utilization. Therefore, it is necessary to find suitable supports to prepare catalysts in which noble metals are uniformly dispersed and less prone to agglomeration, and then further study their performance as catalysts for the selective hydrogenation of unsaturated hydrocarbons.

[0006] The preparation methods for highly efficient catalysts include: ① adding other metals to noble metal catalysts to modify the catalyst, reducing the adsorption capacity of the active sites of the catalyst for monoolefins, thereby improving the hydrogenation selectivity of the catalyst that generates monoolefins; ② modifying the support so that the generated monoolefins can easily and quickly leave the catalyst surface, avoiding further hydrogenation of monoolefins to form alkanes.

[0007] Typically, supported Pd catalysts and liquid-phase fixed-bed hydrogenation processes are used to pretreat alkylation feedstocks. Because butene in C4 hydrocarbons can be hydrogenated in addition to butadiene, it can also be hydrogenated to the corresponding alkanes, leading to butene loss. While the noble metal Pd exhibits selective hydrogenation properties, its own hydrogenation activity is also quite strong. Using Pd alone as a catalyst will result in the hydrogenation of some butene. Therefore, it is often necessary to appropriately modify the Pd catalyst to reduce its hydrogenation activity towards butene while simultaneously increasing its isomerization activity towards 1-butene.

[0008] Furthermore, during the selective hydrodediene addition process of mixed C4 feedstock, the feedstock contains a certain amount of sulfur (10-200 μg / g). Sulfur compounds can poison the selective hydrodediene catalyst, causing its activity to decline rapidly and severely affecting the catalyst's operating cycle. Moreover, sulfides from the mixed C4 feedstock can enter the composite product, causing the sulfur content of gasoline blending components to fail to meet the China V and China VI emission standards.

[0009] Currently, the main method for removing sulfides from mixed C4 is to perform rough desulfurization using solid alkali, followed by the removal of various sulfides in one step using hydrolysants or adsorbents.

[0010] Patent application CN101249366A discloses a method for fine desulfurization. First, refinery C4 components undergo coarse desulfurization using a solid alkali. Then, they are contacted with a carbonyl sulfide adsorbent to adsorb and remove most of the carbonyl sulfides and mercaptans. Finally, they are contacted with a fine desulfurization adsorbent to adsorb and remove any remaining sulfur. After fine desulfurization treatment using the method provided by this invention, the total sulfur content of the refinery's C4 components can be reduced to 1 mg / m³.3 the following.

[0011] Patent application CN103102987A discloses a method for fine desulfurization of C4 fractions. Liquefied petroleum gas (LPG) from byproducts of catalytic cracking and catalytic pyrolysis units is desulfurized by amine washing and desulfurized by alkali washing. The gas is then separated into C3 components by a gas separation unit. The mixed C4 fraction from the gas separation unit is separated at the top of a light-light fraction removal tower to obtain a fraction rich in isobutane and trace amounts of carbonyl sulfide (COS). The remaining fraction enters a heavy fraction removal tower. At the top of the heavy fraction removal tower, a refined mixed C4 fraction rich in butene is separated, with a sulfur content of less than 3 mg / m³. 3 .

[0012] Patent application TW201011100A discloses a method for removing thiols from a gas phase mixture. First, a gas phase mixture containing hydrocarbons and thiols is fed into a reactor, and an etherification reaction is carried out using a catalyst containing palladium and silver. After etherification, the reactor product mixture is fractionated to separate the hydrocarbons with lower boiling points from the thioethers, thereby achieving the purpose of desulfurization.

[0013] Non-precious metal butadiene selective hydrogenation catalysts are relatively inexpensive and have better resistance to impurities and poisons than precious metal catalysts, especially for sulfur-containing compounds, and can be used to process sulfur-containing C4 feedstocks. However, the activity of current non-precious metal butadiene selective hydrogenation catalysts is not high. Summary of the Invention

[0014] The purpose of this invention is to overcome the poor selective hydrogenation performance and 1-butene isomerization performance of non-precious metal catalysts in the prior art. This invention provides a non-precious metal hydrogenation catalyst, its preparation method and application, and methods for selective hydrogenation and 1-butene isomerization of butadiene. This catalyst exhibits good activity and excellent selectivity in hydrogenation and skeletal isomerization, thus improving the hydrogenation performance of butadiene. Furthermore, the use of a non-precious metal as the active metal reduces costs and improves resource utilization. Compared to palladium hydrogenation catalysts, it has better resistance to impurities and poisons, especially for sulfur-containing compounds, demonstrating good adaptability.

[0015] To achieve the above objectives, a first aspect of the present invention provides a non-precious metal hydrogenation catalyst, wherein the catalyst comprises an active metal and a support, wherein the support comprises alumina, a molecular sieve having a BEA structure, and a modified metal oxide, wherein the modified metal oxide is at least one selected from titanium oxide, zirconium oxide, and cerium oxide; wherein the modified metal oxide has η < 0.3 and θ ≥ 50, where η = weight percentage of crystalline phase modified metal oxide in the support / weight percentage of chemical composition of modified metal oxide in the support, and θ = weight percentage of modified metal oxide on the surface of the support / weight percentage of chemical composition of modified metal oxide in the support, wherein titanium oxide is calculated as TiO2, cerium oxide as CeO2, and zirconium oxide as ZrO2; wherein the active metal comprises Cu and optionally other metal components; wherein the other metal components are at least one selected from Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca, and W.

[0016] A second aspect of the present invention provides a method for preparing a non-precious metal hydrogenation catalyst, wherein the method comprises the following steps:

[0017] (1) Alumina, molecular sieve with BEA structure, water and acid solution are brought into contact to form a slurry; the slurry is then successively shaped, dried and calcined to form a mixed matrix carrier;

[0018] (2) The mixed matrix carrier obtained in step (1) is brought into contact with the gas-carried modified metal oxide precursor gas flow to obtain a mixed matrix loaded with modified metal oxide precursor.

[0019] (3) Hydrolyze the mixed matrix of the loaded modified metal oxide precursor, calcine it, and obtain the support;

[0020] (4) The support is impregnated with an active metal precursor solution to obtain a support containing an active metal precursor; the active metal includes Cu and optionally other metal components; wherein the other metal components are at least one of Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca and W;

[0021] (5) Dry and calcine the carrier containing the active metal precursor;

[0022] The modified metal oxide is at least one of titanium oxide, zirconium oxide, and cerium oxide.

[0023] The third aspect of this invention provides the application of the non-precious metal hydrogenation catalyst described in the first aspect in the selective hydrogenation of butadiene and the isomerization reaction of 1-butene.

[0024] The fourth aspect of the present invention provides a method for selective hydrogenation of butadiene and 1-butene isomerization, wherein the method includes contacting a butadiene-containing feedstock with the non-precious metal catalyst described in the first aspect to carry out a hydrogenation reaction.

[0025] Preferably, the butadiene-containing feedstock is C4 by-product from sulfur-containing FCC in a refinery or C4 raffinate from ethylene cracking.

[0026] Preferably, the butadiene-containing raw material is a hydrogen-containing stream, with the following volume fractions: hydrogen gas fraction 1-10%, 1,3-butadiene volume fraction 1-5%, 1-butene volume fraction 15-30%, n-butane volume fraction 15-30%, other gases as carrier gases (e.g., nitrogen), and thiol content 10-200 ppm.

[0027] The non-precious metal hydrogenation catalyst for selective hydrogenation of butadiene and isomerization of 1-butene provided by this invention has the active metal being the non-precious metal component Cu and optionally other metal components, which can reduce costs and has higher activity than existing non-precious metal catalysts. At the same time, it has better resistance to impurities and poisons than palladium hydrogenation catalysts, especially for sulfur-containing compounds, and has better adaptability. In addition, it also has the advantage of high selectivity for n-butene isomerization.

[0028] The catalyst preparation method provided by this invention involves first preparing a support with a relatively low η value and a relatively high θ value, and then loading an active non-precious metal component as the active metal. The preparation method is easy to implement. Attached Figure Description

[0029] Figure 1 These are XRD patterns of supports containing alumina, β-zeolite, and titanium oxide. Specifically, 1 is the XRD pattern of the support prepared in Example 1 of this invention; 2 is the XRD pattern of the alumina-supported titanium oxide support prepared by impregnation with modified metallic TiO2 in Comparative Example 4 of this invention; and 3 is the XRD pattern of the physical mixture of alumina and titanium dioxide prepared in Comparative Example 3 of this invention.

[0030] In the XRD curve, the diffraction peaks of TiO2 (anatase) are located at 2θ = 25.37°, 48.12°, 53.97°, and 55.1°. Detailed Implementation

[0031] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0032] The first aspect of this invention provides a non-precious metal hydrogenation catalyst, wherein the catalyst comprises an active metal and a support, wherein the support comprises alumina, a molecular sieve having a BEA structure, and a modified metal oxide, wherein the modified metal oxide is at least one selected from titanium oxide, zirconium oxide, and cerium oxide; wherein the modified metal oxide has η < 0.3 and θ ≥ 50, where η = weight percentage of crystalline phase modified metal oxide in the support / weight percentage of chemical composition of modified metal oxide in the support, and θ = weight percentage of modified metal oxide on the surface of the support / weight percentage of chemical composition of modified metal oxide in the support, wherein titanium oxide is calculated as TiO2, cerium oxide as CeO2, and zirconium oxide as ZrO2; wherein the active metal comprises Cu and optionally other metal components; wherein the other metal components are at least one selected from Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca, and W.

[0033] In a preferred embodiment, the other metal component is selected from at least one of Ni, Fe, Mo and Co.

[0034] The non-precious metal hydrogenation catalyst provided by this invention is used in the selective hydrogenation of butadiene and the isomerization reaction of 1-butene. The active metal is a non-precious metal component, which has higher activity and better resistance to impurities and poisons than existing non-precious metal catalysts, especially showing good adaptability to sulfur-containing compounds. In addition, it also has the advantage of high selectivity for n-butene isomerization.

[0035] In this invention, the content of each substance in the catalyst is not specifically limited. Preferably, based on the total amount of catalyst, the content of the active metal is 5-40% by weight, and the content of the support is 60-95% by weight; more preferably, based on the total amount of catalyst, the content of the active metal is 10-35% by weight, and the content of the support is 65-90% by weight. The advantage of this preferred embodiment is that it provides good butadiene hydrogenation selectivity while also exhibiting high 1-butene skeletal isomerization activity.

[0036] In this invention, Cu and optionally other metal components can be selected as the active metals of the catalyst, and there are no specific limitations on their content. Preferably, based on the total amount of catalyst, the content of Cu (calculated as CuO) is 5-30% by weight, and the content of other metal components (calculated as oxides) is 3-20% by weight; more preferably, based on the total amount of catalyst, the content of Cu (calculated as CuO) is 5-25% by weight, and the content of other metal components (calculated as oxides) is 5-15% by weight. The advantage of this preferred embodiment is that it has better activity stability. Cu has weak hydrogen dissociation activity and is prone to diene adsorption on the Cu surface, leading to carbon deposition and catalyst deactivation. Other metal components, such as Ni, can produce a hydrogen spillover effect with Cu. Hydrogen dissociation on Ni produces hydrogen free radicals that spill over to the Cu surface, enhancing its hydrogenation activity for butadiene and suppressing the strong and excessive adsorption capacity of individual Cu active sites for unsaturated hydrocarbons.

[0037] In this invention, the amount of each substance in the support is not specifically limited, as long as the desired support can be obtained and thus a non-precious metal catalyst can be obtained. Preferably, based on the total amount of the support, the content of alumina is 50-90% by weight, the content of molecular sieve with BEA structure is 2-40% by weight, and the content of modified metal oxide is 1-40% by weight; more preferably, the content of alumina is 60-80% by weight, the content of molecular sieve with BEA structure is 10-30% by weight, and the content of modified metal oxide is 2-15% by weight. The advantage of this preferred embodiment is that the specific surface area of ​​the support is large and the acid content is suitable.

[0038] In a preferred embodiment, the modified metal oxide in the support is titanium oxide. Preferably, based on the total amount of the support, the content of titanium oxide, calculated as TiO2, is 2-20 wt%, for example 5-15 wt%, 5-10 wt%, 2.5-17 wt%, or 3-13 wt%; the content of zirconium oxide, calculated as ZrO2, is 0-8 wt%, for example 0-6 wt%, 0-5 wt%, 0-3 wt%, or 1-6 wt%; and the content of cerium oxide, calculated as CeO2, is 2-30 wt%, for example 5-15 wt%, 5-10 wt%, 2.5-17 wt%, or 15-25 wt%.

[0039] In a particularly preferred embodiment, the modified metal oxide is titanium dioxide, and the content of titanium oxide, calculated as TiO2, is 2-20% by weight, preferably 5-15% by weight, based on the total amount of the carrier. The advantage of this preferred embodiment is that there is a strong interaction between TiO2 and alumina, resulting in electron transfer, which is beneficial for the stable dispersion of the metal loaded on the carrier.

[0040] According to the present invention, preferably, the modified metal oxide monolayer is dispersed on a mixed matrix of alumina and molecular sieve having a BEA structure.

[0041] In this invention, unless otherwise specified, the percentage content of the crystalline phase modified metal oxide can be measured using the following method: The percentage content of the crystalline phase modified metal oxide is calculated by fitting a modified Rietveld model using X-ray diffraction and phase filtering; for phase filtering, see RVSiriwardane, JAPoston, G. Evans, Jr.Ind.Eng.Chem.Res.33(1994), 2810-2818; for the modified Rietveld model, see RIQAS Rietveld Analysis, Operation Manual, Material Data, Inc., Berkley, CA (1999). The percentage content of the chemical composition of the modified metal oxide is the total content of the modified metal oxide in the support, and the percentage content of the chemical composition of the modified metal oxide can be determined by X-ray fluorescence or chemical analysis.

[0042] In this invention, the weight percentage of modified metal oxide on the carrier surface is measured by XPS method, and the measured surface layer thickness is within a 5nm range from the outer surface.

[0043] In this invention, there are no specific limitations on the structure of alumina. Preferably, the catalyst has a phase structure of at least one of γ-alumina, η-alumina, p-alumina, and χ-alumina. The advantage of this preferred embodiment is that it exhibits better activity stability.

[0044] According to the present invention, preferably, the modified metal oxide has an n of 0 and an θ of 50-95, more preferably, an θ of 60-90. The advantage of this preferred embodiment is that the modified metal is dispersed in a monolayer on the alumina surface, forming more modification sites.

[0045] According to the present invention, preferably, the ratio of the Brønsted acid to the Lewis acid in the support is not less than 0.5; more preferably, the ratio is 0.5-5; and even more preferably, it is 0.8-1.5. The advantage of this preferred embodiment is that the support has acid centers of suitable strength, resulting in high selectivity for the butene isomerization reaction.

[0046] In this invention, Brønsted acid and Lewis acid are determined by characterizing the acidity of the catalyst surface using infrared spectroscopy.

[0047] According to the present invention, preferably, the catalyst has a specific surface area of ​​100-450 m². 2 / g, with a pore volume of 0.3-2.0 mL / g; more preferably, the catalyst has a specific surface area of ​​120-350 m² / g. 2 / g, with a pore volume of 0.5-1.2 mL / g. The advantage of this preferred embodiment is that it has both a high specific surface area and a large pore volume, which is beneficial for reactant adsorption and diffusion, thus increasing reactivity.

[0048] In this invention, the specific surface area and pore volume of the catalyst are measured by BET testing.

[0049] A second aspect of the present invention provides a method for preparing a non-precious metal hydrogenation catalyst, wherein the method comprises the following steps:

[0050] (1) Alumina, molecular sieve with BEA structure, water and acid solution are brought into contact to form a slurry; the slurry is then successively shaped, dried and calcined to form a mixed matrix carrier;

[0051] (2) The mixed matrix carrier obtained in step (1) is brought into contact with the gas-carried modified metal oxide precursor gas flow to obtain a mixed matrix loaded with modified metal oxide precursor.

[0052] (3) Hydrolyze the mixed matrix of the loaded modified metal oxide precursor, calcine it, and obtain the support;

[0053] (4) The support is impregnated with an active metal precursor solution to obtain a support containing an active metal precursor; the active metal includes Cu and optionally other metal components; wherein the other metal components are at least one of Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca and W;

[0054] (5) Dry and calcine the carrier containing the active metal precursor;

[0055] The modified metal oxide is at least one of titanium oxide, zirconium oxide, and cerium oxide.

[0056] The method of the present invention is easy to implement, and compared with the traditional catalyst preparation process, the preparation method simplifies the preparation process and reduces the operating cost.

[0057] According to the method of the present invention, preferably, the amounts of alumina, BEA-structured molecular sieve, modified metal oxide, and active metal are such that, based on the total amount of catalyst, the content of the active metal is 5-40% by weight, and the content of the support is 60-95% by weight; more preferably, based on the total amount of catalyst, the content of the active metal is 10-35% by weight, and the content of the support is 65-90% by weight. The advantage of this preferred embodiment is that it provides good butadiene hydrogenation selectivity while also exhibiting high 1-butene skeletal isomerization activity.

[0058] In a preferred embodiment, based on the total amount of catalyst, the Cu content, calculated as CuO, is 5-30% by weight, and the content of other metal components, calculated as oxides, is 3-20% by weight; more preferably, based on the total amount of catalyst, the Cu content, calculated as CuO, is 5-25% by weight, and the content of other metal components, calculated as oxides, is 5-15% by weight.

[0059] In a preferred embodiment, the other metal component is selected from at least one of Ni, Fe, Mo and Co.

[0060] In this invention, there is no specific limitation on the type of alumina used in step (1), as long as it meets the requirements for preparing a non-precious metal catalyst. Preferably, in step (1), the alumina is selected from at least one of γ-alumina, η-alumina, p-alumina, χ-alumina, and hydrated alumina. More preferably, the alumina is selected from at least one of γ-alumina, η-alumina, p-alumina, and χ-alumina.

[0061] According to the present invention, preferably, the hydrated alumina is one or more selected from boehmite, diaspore, boehmite, gibbsite, bayerite, nordstrandite, and amorphous aluminum hydroxide. Preferably, the average particle size (diameter) of the alumina is 0.5-50 μm, for example, 0.5-30 μm.

[0062] According to the present invention, preferably, the specific surface area of ​​the alumina is 100-300 m². 2 / g, with a pore volume of 0.3-2mL / g; more preferably, the specific surface area of ​​the alumina is 120-350m². 2 / g, with the pore volume preferably being 0.8-1.8 mL / g, for example 0.85-1.2 mL / g.

[0063] The advantages of using alumina in the above preferred embodiment are that it has a high specific surface area and a large pore volume, which is conducive to the dispersion of active metals on it, and also facilitates the timely diffusion of products, reduces carbon deposition, and increases the activity and stability of the catalyst.

[0064] In this invention, there is no specific limitation on the type of molecular sieve with a BEA structure. Preferably, the molecular sieve with a BEA structure is selected from at least one of hydrogen-form β-zeolite molecular sieves, phosphorus-containing β-zeolite molecular sieves, rare earth metal-containing β-zeolite molecular sieves, and β-zeolite molecular sieves containing both phosphorus and rare earth metals, and more preferably hydrogen-form β-zeolite molecular sieves and / or rare earth metal-containing β-zeolite molecular sieves. Preferably, in the rare earth metal-containing β-zeolite molecular sieve, the rare earth element can be at least one of lanthanum, cerium, praseodymium, and neodymium, and more preferably lanthanum and / or cerium. Preferably, in the phosphorus-containing β-zeolite molecular sieve, the phosphorus content is 1-15% by weight, based on the total amount of β-zeolite molecular sieve; in the rare earth metal-containing β-zeolite molecular sieve, the rare earth metal content is 1-10% by weight, based on the total amount of β-zeolite molecular sieve; and in the phosphorus- and rare earth metal-containing β-zeolite molecular sieve, the phosphorus content is 3-10% by weight, and the rare earth metal content is 2-8% by weight, based on the total amount of β-zeolite molecular sieve. The advantage of this preferred embodiment is that the prepared support has a suitable acid content, which makes the catalyst more conducive to butene isomerization.

[0065] According to the present invention, preferably, the ratio of Brønsted acid to Lewis acid in the molecular sieve having a BEA structure is 0.8-3.0, more preferably 0.83-1.25. The advantage of this preferred embodiment is that the support has acid centers of suitable strength, resulting in high selectivity for the butene isomerization reaction.

[0066] According to the present invention, preferably, the molar ratio of silica to alumina in the molecular sieve having the BEA structure is 15-40.

[0067] In a preferred embodiment, the molecular sieve with the BEA structure has a specific surface area of ​​300-750 m². 2 / g, with a pore volume of 0.2-0.8 mL / g, more preferably a specific surface area of ​​500-700 m² / g. 2 / g, with a pore volume of 0.3-0.7 mL / g. The advantages of this preferred embodiment are that the prepared support has a large specific surface area, which is beneficial for the dispersion of active metals, good pore volume, which facilitates the diffusion of raw material molecules, and increases reactivity.

[0068] In this invention, the range of types of acid solutions selected in step (1) is relatively wide. Preferably, the acid solution is selected from water-soluble inorganic acids and / or organic acids, and more preferably at least one of hydrochloric acid, nitric acid, phosphoric acid, and acetic acid.

[0069] In this invention, there is no specific limitation on the concentration of the acid solution in step (1). Preferably, the concentration of the acid solution is 5-40% by weight, more preferably 10-35% by weight.

[0070] In this invention, there is no specific limitation on the amount of acid solution used in step (1). Preferably, the amount of acid solution used results in a pH value of 1-5 for the slurry, and more preferably 1.5-4.

[0071] According to the present invention, preferably, the solid content of the slurry in step (1) is 20-45% by weight.

[0072] According to the present invention, preferably, the specific surface area of ​​the mixed matrix carrier is not less than 150 m². 2 / g, preferably 150-500m 2 / g, further preferably 200-400m 2 / g; More preferably, the pore volume of the mixed matrix carrier is not less than 0.3 mL / g, preferably 0.3-2 mL / g, and more preferably 0.5-1.8 mL / g. Preferably, the specific surface area of ​​the obtained carrier is reduced by ≤15% compared to the specific surface area of ​​alumina.

[0073] In this invention, commonly used carrier molding methods are applicable, such as spray drying, extrusion molding, and spheroidization. Preferably, the molding process of the mixed matrix carrier in this invention can be carried out as follows: the slurry is spray-dried using a spray dryer, and then the resulting microspheres are dried and calcined. Preferably, the spray drying conditions include: a pressure of 5-12 MPa, an inlet temperature of 400-700°C, and an outlet temperature of 100-250°C; more preferably, the pressure is 6-10 MPa, the inlet temperature is 450-600°C, and the outlet temperature is 120-200°C.

[0074] In this invention, the drying conditions in step (1) are selected within a wide range. Preferably, the drying conditions are: a temperature of 50-250℃ and a time of 0.5-5h; more preferably, a temperature of 80-200℃ and a time of 1-4h.

[0075] In this invention, the range of conditions for roasting in step (1) is relatively wide. Preferably, the roasting conditions are: temperature of 400-700℃ and time of 1-12h; more preferably, temperature of 450-650℃ and time of 2-8h.

[0076] According to the present invention, the modified metal oxide precursor is a substance that can be vaporized at room temperature to 350°C to form a gaseous metal oxide precursor.

[0077] In this invention, there are no specific limitations on the type of modified metal oxide precursor in step (2). Preferably, the modified metal oxide precursor is at least one of titanium oxide precursor, zirconium oxide precursor, and cerium oxide precursor, and more preferably titanium oxide precursor. The advantage of this preferred embodiment is that the interaction between the titanium oxide precursor and aluminum oxide is strong, which promotes the dispersion of the active metal while there is electron transfer between the precursor and the supported active metal, thereby promoting the adsorption of butadiene on the surface of the active metal and the hydrogenation selectivity.

[0078] In a preferred embodiment, the titanium dioxide precursor is selected from at least one of titanium tetrachloride, ethyl titanate, tetrabutyl titanate, isopropyl titanate, and titanium acetate; more preferably, the titanium dioxide precursor is titanium tetrachloride.

[0079] In a preferred embodiment, the zirconia precursor is selected from at least one of zirconium tetrachloride, zirconium ethoxide, zirconium methoxide, zirconium isopropoxide, and tetrabutyl zirconate. More preferably, the zirconia precursor is zirconium tetrachloride and / or zirconium methoxide.

[0080] In a preferred embodiment, the cerium oxide precursor is selected from at least one of cerium trichloride, cerium ethoxide, and cerium isopropoxide; more preferably, the cerium oxide precursor is cerium trichloride and / or cerium isopropoxide.

[0081] In a preferred embodiment, the modified metal oxide is titanium oxide, and the content of titanium oxide, calculated as TiO2, is 2-20% by weight, preferably 2-15% by weight, based on the total amount of the carrier. The advantage of this preferred embodiment is that titanium oxide is dispersed in a monolayer on the surface of the carrier, has not yet entered the Al2O3 crystal phase, and has not agglomerated to form TiO2 grains.

[0082] In this invention, a gas stream carrying a modified metal oxide precursor is brought into contact with a mixed matrix carrier. The gas stream includes a gas (also called a carrier gas) and the gaseous modified metal oxide precursor. The gas is an inert gas that does not react with the modified metal oxide precursor. Preferably, in step (2), the gas is an anhydrous inert gas, and the water content in the anhydrous inert gas does not exceed 10 ppm, for example, 3-10 ppm. Preferably, the inert gas is one or more of nitrogen, helium, neon, and argon.

[0083] In a preferred embodiment, the content of modified metal oxide precursor in the gas stream carrying the modified metal oxide precursor is 0.1-5 g / L, preferably 0.5-2 g / L, wherein the content of modified metal oxide precursor is calculated as metal oxide, titanium oxide as TiO2, zirconium oxide as ZrO2, and cerium oxide as CeO2.

[0084] According to the present invention, preferably, in step (2), the gas temperature is room temperature - 350°C, for example, room temperature - 300°C or 15-300°C; the room temperature is 15-40°C; the contact temperature is 15-350°C; and the contact pressure is 0.1-10 atm, preferably 0.1-5 atm. The advantage of this preferred embodiment is that the modified metal oxide precursor is completely and uniformly hydrolyzed.

[0085] According to the present invention, preferably, in step (2), the ratio of the volumetric flow rate of the gas per minute to the volume of the mixed matrix carrier is 10-50:1, more preferably 15-30:1; wherein the volume of the gas is measured in terms of volume under standard conditions, and the volume of the mixed matrix carrier is measured in terms of bulk volume.

[0086] In a preferred embodiment, the mixed matrix carrier described in step (2) is in contact with the gas-carried modified metal oxide precursor gas flow (hereinafter also referred to as the gas flow) in a fluidized state, or the mixed matrix carrier is in contact with the gas flow in a fixed bed, or in contact with the gas flow under stirring; the fluidized state is a bubbling bed, a turbulent bed, a fast bed, or a conveying bed.

[0087] In a preferred embodiment, in step (2), alumina is contacted with a gas-carried modified metal oxide precursor gas stream, wherein the gas stream and the mixed matrix carrier are contacted in a fluidized bed, and the contact volume hourly space velocity is 3-80:1 min. -1 Preferably 5-30:1min -1 For example, 10-25: 1min -1 The volumetric flow rate of the gas flow is measured by the volume of the gas under standard conditions, the alumina and molecular sieve mixed matrix carrier with BEA structure are measured by the bulk volume, and the fluidized bed can be a dispersed fluidized bed, a bubble bed, or a turbulent bed.

[0088] In this invention, when the modified metal oxide precursor on the alumina and BEA-structured molecular sieve mixed matrix support reaches a preset loading amount, contact with the gas-carried modified metal oxide precursor gas flow is stopped, resulting in a mixed matrix loaded with the modified metal oxide precursor. The contact time between the alumina and BEA-structured molecular sieve mixed matrix support and the gas-carried modified metal oxide precursor gas flow is called the loading time.

[0089] In this invention, the hydrolysis of the mixed matrix typically involves contacting the mixed matrix carrier loaded with the modified metal oxide precursor with a gas containing water vapor, so that the modified metal oxide precursor comes into contact with water, thereby hydrolyzing the modified metal oxide precursor into hydrolysis products. Preferably, in step (3), the hydrolysis of the mixed matrix loaded with the modified metal oxide precursor is prepared by the following method: contacting the mixed matrix loaded with the modified metal oxide precursor with a gas containing water vapor, wherein the ratio of the gas containing water vapor to the mixed matrix (the ratio of the gas containing water vapor to the bulk volume of the mixed matrix under standard conditions) is 10-50:1, preferably 15-30:1, the proportion of water vapor in the gas containing water vapor to the total volume of the gas is 0.1-100% by volume, preferably 3-100% by volume, for example 10-70% by volume, and the other gases in the gas containing water vapor are at least one of inert gas, nitrogen, and air; preferably, the hydrolysis time is 1-50 h, more preferably 2-30 h. The hydrolysis time is usually greater than or equal to the loading time.

[0090] In this invention, there are no specific restrictions on the calcination conditions. Preferably, in step (3), the calcination temperature is 400-700℃ and the calcination time is 1-12h. More preferably, the calcination temperature is 450-650℃ and the calcination time is 2-8h.

[0091] According to the present invention, preferably, in step (3), the roasting atmosphere can be an atmosphere containing oxygen or an atmosphere without oxygen.

[0092] In a preferred embodiment, the oxygen content in the oxygen-containing atmosphere can be 3-100% by volume, for example, an air atmosphere or an oxygen atmosphere.

[0093] In this invention, there are no specific limitations on the types of active metal precursors in step (4), and all active metal precursors conventionally defined in the art are applicable to this invention. Preferably, the active metal precursor is selected from at least one of metal nitrates, acetates, metal chlorides, metal carbonates, metal acetate complexes, metal hydroxides, metal oxalate complexes, high-valent metal acids, high-valent metal salts, and metal complexes; more preferably, at least one of metal nitrates, high-valent metal salts, high-valent metal acids, and acetates; and even more preferably, at least one of nitrates, acetates, and high-valent metal salts.

[0094] In a preferred embodiment, the high-valent metal acid salt is selected from at least one of copper chloride, copper nitrate, and copper acetate. The advantage of this preferred embodiment is that the noble metal is highly dispersed on the support, resulting in good reactivity.

[0095] In this invention, step (4) involves impregnating the support with a solution containing an active metal precursor. This typically includes dissolving the active metal precursor in water to form an impregnation solution, and then impregnating the support with the impregnation solution to obtain a support impregnated with the active metal component precursor. Impregnation methods conventionally defined in the art are applicable to this invention, such as equal-volume impregnation and / or excess impregnation. Preferably, when the catalyst contains two or more active metals, the active metal precursor can be introduced onto the support by co-impregnation or stepwise impregnation. For example, it can be prepared by co-impregnation: different active metal precursors (Cu precursor and other metal component precursors) are dissolved together in water, and the pH value of the mixed solution is adjusted with an acid solution to form an impregnation solution. The impregnation solution is then mixed with the support to impregnate the active metal precursor onto the support, followed by drying and calcination. Alternatively, it can be prepared by stepwise impregnation: Each active metal precursor (Cu precursor and other metal component precursors) is dissolved separately in water, and the pH of the mixed solution is adjusted with an acid solution to obtain an impregnation solution. This solution is then contacted with the carrier separately, impregnating the active metal precursor onto the carrier. After each impregnation, the resulting carrier must be dried and calcined. There is no specific restriction on the order in which different active metal precursors are introduced in this invention. For example, the Cu precursor and other metal component precursors can be separately dissolved in water, and the pH of the mixed solution can be adjusted with an alkaline solution to prepare an impregnation solution, which is then used to impregnate the carrier sequentially. Each active metal precursor is impregnated onto the carrier separately, and after each impregnation, the resulting carrier must be dried and optionally calcined. In a preferred embodiment, the water is at least one of deionized water, distilled water, and decationized water.

[0096] In a preferred embodiment, the pH of the solution containing Cu and optionally other metal precursor active metals is 2-4.

[0097] In a preferred embodiment, the pH is adjusted by introducing an acid solution (preferably hydrochloric acid) into the solution containing Cu and optionally other metal precursor active metals. Preferably, the concentration of the hydrochloric acid solution is 10-30% by weight.

[0098] In a preferred embodiment, in step (4), the liquid / solid volume ratio of the impregnation liquid to the carrier is 0.5-5.0, preferably 1.0-4.0; the impregnation temperature is 10-150℃, preferably 20-100℃; and the time is 1-24h, preferably 2-12h.

[0099] In this invention, the impregnated carrier is dried and then calcined. There are no specific restrictions on the drying and calcination conditions in this invention. Preferably, in step (5), the drying temperature is 50-250℃ and the time is 1-24h; more preferably, the drying temperature is 80-200℃ and the time is 2-15h.

[0100] In a preferred embodiment, in step (5), the calcination temperature is 400-700℃ and the calcination time is 0.5-12h. More preferably, the calcination temperature is 500-650℃ and the calcination time is 2-8h. The advantage of this preferred embodiment is that the active metal is basically dispersed on the surface of the carrier in the form of oxides, and there is no excessive sintering.

[0101] The third aspect of this invention provides the application of the non-precious metal hydrogenation catalyst described in the first aspect in the selective hydrogenation of butadiene and the isomerization reaction of 1-butene.

[0102] The fourth aspect of the present invention provides a method for selective hydrogenation of butadiene and 1-butene isomerization, wherein the method includes contacting a butadiene-containing feedstock with the non-precious metal catalyst described in the first aspect to carry out a hydrogenation reaction.

[0103] In a preferred embodiment, the conditions for the selective hydrogenation of butadiene and the 1-butene isomerization reaction include: a reaction temperature of 100-350°C, a pressure of 0.05-3 MPa, and a weight hourly space velocity of 0.5-50 h⁻¹. -1 More preferably, the reaction temperature is 190-300℃, the pressure is 0.1-2.0MPa, and the weight hourly space velocity is 3-20h. -1 The catalyst provided by this invention is particularly suitable for higher reaction temperatures and exhibits good catalytic performance at the preferred reaction temperature of this invention.

[0104] In a preferred embodiment, the butadiene-containing feedstock is C4 by-product from sulfur-containing FCC in a refinery or C4 raffinate from ethylene cracking.

[0105] According to one specific embodiment of the present invention, the reaction is carried out in a fixed-bed microreactor under hydrogen-containing conditions. Preferably, the butadiene-containing feedstock is a hydrogen-containing stream, with the following volume fractions: hydrogen gas fraction 1-10%, 1,3-butadiene volume fraction 1-5%, 1-butene volume fraction 15-30%, n-butane volume fraction 15-30%, other gases as carrier gases (e.g., nitrogen), and thiol content 10-200 ppm.

[0106] In a preferred embodiment, the catalyst may be reduced before use. The present invention does not particularly limit the conditions for the reduction. Preferably, reduction may be performed for 1-5 hours in a hydrogen-containing atmosphere (hydrogen and optionally at least one of nitrogen, helium, argon and neon, preferably nitrogen, with a hydrogen content preferably not less than 5% by volume) at 150-500°C.

[0107] The present invention will be described in detail below through embodiments.

[0108] In the examples and comparative examples, the properties of some of the raw materials used are as follows:

[0109] SB powder: Sasol GmbH, Germany, solids content 75% by weight.

[0110] P25 (titanium dioxide): Degussa, Germany, solid content 98% by weight.

[0111] Metal salts and metal salts were purchased from Sinopharm Chemical Reagents Beijing Co., Ltd.

[0112] In all the embodiments and comparative examples, the composition of the supported butadiene selective hydrogenation and 1-butene isomerization catalysts was determined by X-ray fluorescence spectrometry, the products of butadiene selective hydrogenation and 1-butene isomerization were obtained by chromatographic analysis, and the purity of hydrogen was obtained by gas chromatography analysis.

[0113] The selective hydrogenation of butadiene and 1-butene isomerization experiments of the embodiments and comparative examples of the present invention were carried out in a fixed-bed reactor.

[0114] All X-ray diffraction measurements were performed using a Philips XRG3100 generator equipped with a long, thin, focusing copper X-ray source driven at 40 kV and 30 mA, a Philips 3020 digital goniometer, a Philips 3710MPD control computer, and a Kevex PSI Peltier cooled silicon detector. The Kevex detector was operated using a Kevex 4601 ion pump controller, a Kevex 4608 Peltier power supply, a Kevex 4621 detector bias, a Kevex 4561A pulse processor, and a Kevex 4911-A single-channel analyzer. Diffraction patterns were obtained using Philips APD 4.1C software. All Rietveld calculations were performed using Material Data, Inc. Riqas 3.1C software (Qutokumpu HSC Chemistry for Windows; User Manual, Qutokumpu Research Oy, Pori, Finland (1999)).

[0115] The XPS experiment was performed on a Thermo Fisher ESCALab 250 X-ray photoelectron spectrometer. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV and a power of 150 W. The transmission energy used for the narrow scan was 30 eV. The baseline vacuum during analysis was approximately 6.5 × 10⁻⁶. -10 mbar. The binding energy was corrected using the C1s peak (284.8 eV) of contaminated carbon. The weight percentage of modified metal oxides on the support surface was determined by measuring 10 sample particles and taking the average value.

[0116] Determination of Brønsted (B) and Lewis (L) acids: The acidity of the catalyst surface was characterized using a Nicolet 560 infrared spectrometer (Nicolet, Inc., USA), with wavenumbers of 1400-1700 cm⁻¹. -1 The Brønsted acid in the catalyst is present at 1540 cm⁻¹. -1 Characterized by the characteristic peaks, the L acid in the catalyst has a peak at 1450 cm⁻¹. -1 Characterized by the characteristic peaks, the ratio of Brønsted acid to Lewis acid is calculated by integrating the corresponding peak areas. The ratio of Brønsted acid to Lewis acid is the ratio of the peak area of ​​the characteristic peak of Brønsted acid to the peak area of ​​the characteristic peak of Lewis acid.

[0117] Examples and comparative examples of carrier preparation

[0118] Preparation Example 1

[0119] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 / g, with a pore volume of 1.12mL / g, γ-Al2O3 and β molecular sieve (specific surface area 685.5m²) were added. 2 The microspheres, with a pore volume of 0.38 mL / g, a Brønsted acid to Lewis acid ratio of 1.03, and a silica-alumina molar ratio of 27, are reacted with water and an acid solution (30% hydrochloric acid, chemically pure, produced by Beijing Chemical Plant) to form a slurry (solid content 28% by weight, pH = 2.1). The slurry is then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 9.5 MPa, an inlet temperature of 500°C, and an outlet temperature of approximately 150°C). The microspheres obtained from the spray drying are first dried at 180°C for 1 hour, then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​231.5 m². 2 / g, pore volume is 1.05mL / g.

[0120] 500g of the above-mentioned mixed matrix carrier was placed in a fluidized bed reactor (reactor diameter 10cm, height 40cm). Titanium tetrachloride was placed in a 20℃ constant temperature bath. Nitrogen gas (temperature 25℃) was passed through the titanium tetrachloride at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization for 1 hour, the flow of nitrogen gas through the titanium tetrachloride bath was stopped. Nitrogen gas (temperature 25℃) was then passed through deionized water placed in a 50℃ constant temperature bath at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. Hydrolysis was carried out for 4 hours to obtain the hydrolyzed carrier. The hydrolyzed carrier was calcined in air at 550℃ for 4 hours to obtain the carrier, named S-1. The amounts of the above-mentioned substances, the content of each substance in the carrier, and the properties of the carrier are shown in Table 1. The XRD pattern of the carrier is shown in Table 1. Figure 1 As shown.

[0121] Preparation Example 2

[0122] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 / g, with a pore volume of 1.12mL / g, γ-Al2O3 and Reβ molecular sieve (Re is lanthanum, content is 5.3% by weight, specific surface area is 675.5m²) were added. 2 The microspheres, with a pore volume of 0.41 mL / g, a Brønsted acid to Lewis acid ratio of 1.11, and a silica-alumina molar ratio of 35, are reacted with water and an acid solution (15% wt% nitric acid (chemically pure, produced by Beijing Chemical Plant)) to form a slurry (solid content 28% wt%, pH = 2.1). The slurry is then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 7.5 MPa, inlet temperature of 480°C, and outlet temperature of approximately 150°C). The microspheres obtained from the spray drying are first dried at 180°C for 1 hour, then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​278.5 m². 2 / g, pore volume is 1.01mL / g.

[0123] 500g of the above-mentioned mixed matrix carrier was placed in a fluidized bed reactor (reactor diameter 10cm, height 40cm). Titanium tetrachloride was placed in a 20℃ constant temperature bath. Nitrogen gas (temperature 25℃) was passed through the titanium tetrachloride at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization for 3 hours, the flow of nitrogen gas through the titanium tetrachloride bath was stopped. Nitrogen gas (temperature 25℃) was then passed through deionized water placed in a 50℃ constant temperature bath at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization, hydrolysis was performed for 10 hours to obtain the hydrolyzed carrier. The hydrolyzed carrier was calcined in air at 550℃ for 4 hours to obtain the carrier, named S-2. The amounts of the above substances resulted in the content of each substance in the carrier and the properties of the carrier, as shown in Table 1.

[0124] Preparation Example 3

[0125] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 / g, with a pore volume of 1.12mL / g, γ-Al₂O₃ and Hβ molecular sieve (specific surface area 688.4m²) were added. 2The microspheres, with a pore volume of 0.36 mL / g, a Brønsted acid to Lewis acid ratio of 1.25, and a silica-alumina molar ratio of 18, are reacted with water and an acid solution (15% hydrochloric acid (chemically pure, produced by Beijing Chemical Plant)) to form a slurry (solid content 28% by weight, pH = 2.1). The slurry is then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 8.5 MPa, an inlet temperature of 500°C, and an outlet temperature of approximately 150°C). The microspheres obtained from the spray drying are first dried at 180°C for 1 hour, then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​336.8 m². 2 / g, pore volume is 0.87mL / g.

[0126] 500g of the above-mentioned mixed matrix carrier was placed in a fluidized bed reactor (reactor diameter 10cm, height 40cm). Titanium tetrachloride was placed in a 20℃ constant temperature bath. Nitrogen gas (temperature 25℃) was passed through the titanium tetrachloride at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization for 7 hours, the flow of nitrogen gas through the titanium tetrachloride bath was stopped. Nitrogen gas (temperature 25℃) was then passed through deionized water placed in a 50℃ constant temperature bath at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization, hydrolysis was performed for 25 hours to obtain the hydrolyzed carrier. The hydrolyzed carrier was calcined in air at 550℃ for 4 hours to obtain the carrier, named S-3. The amounts of the above-mentioned substances resulted in the content of each substance in the carrier and the properties of the carrier, as shown in Table 1.

[0127] Preparation Example 4

[0128] Following the method of Preparation Example 3, except that titanium tetrachloride and zirconium tetrachloride were placed in a constant temperature bath at 20°C, respectively. Nitrogen gas (at 25°C) was passed sequentially through titanium tetrachloride and zirconium tetrachloride at a flow rate of 10 L / min before entering the fluidized bed reactor from the bottom. After fluidization for 6 hours, the flow of nitrogen gas through the titanium tetrachloride and zirconium tetrachloride bath was stopped. Nitrogen gas (at 25°C) was then passed through deionized water placed in a constant temperature bath at 50°C at a flow rate of 10 L / min before entering the fluidized bed reactor from the bottom. After fluidization, hydrolysis was performed for 30 hours to obtain the hydrolyzed support. The hydrolyzed support was calcined in air at 550°C for 4 hours to obtain the support, named S-4. The amounts of the above substances resulted in the content of each substance in the support and the properties of the support, as shown in Table 1.

[0129] Preparation Example 5

[0130] Following the method of Preparation Example 3, the difference was that titanium tetrachloride and cerium trichloride were placed in a constant temperature bath at 20°C, respectively. Nitrogen gas (temperature 25°C) was passed sequentially through titanium tetrachloride and cerium trichloride at a flow rate of 10 L / min before entering the fluidized bed reactor from the bottom. After fluidization for 6 hours, the passage of nitrogen gas through the titanium tetrachloride and zirconium tetrachloride bath was stopped. Nitrogen gas (temperature 25°C) was then passed through deionized water placed in a constant temperature bath at 50°C at a flow rate of 10 L / min before entering the fluidized bed reactor from the bottom. After fluidization, hydrolysis was performed for 30 hours to obtain the hydrolyzed support. The hydrolyzed support was calcined in air at 550°C for 4 hours to obtain the support, named S-5. The amounts of the above substances resulted in the content of each substance in the support and the properties of the support, as shown in Table 1.

[0131] Preparation of Comparative Example 1

[0132] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 The microspheres, with a pore volume of 1.12 mL / g, were prepared by contacting γ-Al₂O₃, water, and an acid solution (30% hydrochloric acid, chemically pure, produced by Beijing Chemical Plant) to form a slurry (solid content 28% by weight, pH = 2.1). The slurry was then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 8.5 MPa, inlet temperature of 480°C, and outlet temperature of approximately 150°C). The microspheres obtained from the spray drying were first dried at 180°C for 1 hour, and then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​181.5 m². 2 / g, pore volume 1.12mL / g; the resulting carrier was named DS-1. The amounts of the above substances resulted in the content of each substance in the carrier and the properties of the carrier, as shown in Table 1.

[0133] Preparation of Comparative Example 2

[0134] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 / g, with a pore volume of 1.12mL / g, γ-Al₂O₃ and Reβ molecular sieve (Re is cerium, content is 5.5% by weight, specific surface area is 675.5m²) were added. 2The microspheres, with a pore volume of 0.41 mL / g, a Brønsted acid to Lewis acid ratio of 1.11, and a silica-alumina molar ratio of 35, are reacted with water and an acid solution (15% wt% nitric acid (chemically pure, produced by Beijing Chemical Plant)) to form a slurry (solid content 28% wt%, pH = 2.1). The slurry is then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 8.0 MPa, an inlet temperature of 475°C, and an outlet temperature of approximately 150°C). The microspheres obtained from the spray drying are first dried at 180°C for 1 hour, then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​278.5 m². 2 / g, pore volume 1.01mL / g; the resulting carrier was named DS-2. The amounts of the above substances resulted in the content of each substance in the carrier and the properties of the carrier, as shown in Table 1.

[0135] Preparation of Comparative Example 3

[0136] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 / g, with a pore volume of 1.12mL / g, γ-Al₂O₃ and Hβ molecular sieve (specific surface area 688.4m²) were added. 2 The microspheres, with a pore volume of 0.36 mL / g, a Brønsted acid to Lewis acid ratio of 1.25, and a silica-alumina molar ratio of 18, are reacted with water and an acid solution (15% hydrochloric acid (chemically pure, produced by Beijing Chemical Plant)) to form a slurry (solid content 28% by weight, pH = 2.1). The slurry is then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 7.8 MPa, an inlet temperature of 490°C, and an outlet temperature of approximately 150°C). The microspheres obtained from the spray drying are first dried at 180°C for 1 hour, then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​336.8 m². 2 / g, with a pore volume of 0.87mL / g; physically mixed with TiO2 and calcined at 550℃ for 4h in air atmosphere to obtain the support, named DS-3. The amounts of the above substances resulted in the content of each substance in the support and the properties of the support are shown in Table 1. The XRD pattern of the support is shown in... Figure 1 As shown.

[0137] Preparation of Comparative Example 4

[0138] Following the method of Preparation Example 3, the difference lies in that tetrabutyl titanate was mixed and stirred with deionized water for 30 min, and then impregnated onto the mixed matrix support by an equal volume impregnation method. The mixture was then calcined in air at 550°C for 4 h to obtain the support, which was named DS-4. The amounts of the above-mentioned substances, resulting in the content of each substance in the support and the properties of the support, are shown in Table 1. The XRD pattern of the support is shown in... Figure 1 As shown.

[0139] Preparation of Comparative Example 5

[0140] SB powder was calcined at 500℃ for 4 hours to obtain γ-Al2O3, which has a specific surface area of ​​182 m². 2 The microspheres, with a pore volume of 1.12 mL / g, were prepared by contacting γ-Al₂O₃, water, and an acid solution (15% wt% nitric acid (chemically pure, produced by Beijing Chemical Plant)) to form a slurry (solid content 28% wt%, pH = 2.1). The slurry was then shaped (by spray drying using a Niro Bowen Nozzle Tower™ spray dryer at a pressure of 8.3 MPa, inlet temperature of 500°C, and outlet temperature of approximately 150°C). The microspheres obtained from the spray drying were first dried at 180°C for 1 hour, and then calcined at 635°C for 1 hour to form a mixed matrix carrier with a specific surface area of ​​181.5 m². 2 / g, pore volume is 1.12mL / g.

[0141] 500g of the above-mentioned mixed matrix carrier was placed in a fluidized bed reactor (reactor diameter 10cm, height 40cm). Titanium tetrachloride was placed in a 20℃ constant temperature bath. Nitrogen gas (temperature 25℃) was passed through the titanium tetrachloride at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization for 3 hours, the nitrogen gas flow through the ethyl titanate bath was stopped. Nitrogen gas (temperature 25℃) was then passed through deionized water placed in a 50℃ constant temperature bath at a flow rate of 10L / min and then entered the fluidized bed reactor from the bottom. After fluidization, hydrolysis was performed for 9 hours to obtain the hydrolyzed carrier. The hydrolyzed carrier was calcined in air at 550℃ for 4 hours to obtain the carrier, named DS-5. The amounts of the above substances resulted in the content of each substance in the carrier and the properties of the carrier, as shown in Table 1.

[0142] Table 1

[0143]

[0144]

[0145] Note: The carrier composition is the result of XRF measurement of modified metal oxide values ​​and alumina normalized. The contents of SiO2, Al2O3, TiO2, ZrO2, CeO2 and BEA-structured molecular sieves in Table 1 are based on the total amount of the carrier. Among them, the content of Al2O3 comes partly from BEA-structured molecular sieves and partly from SB powder.

[0146] Catalyst Examples and Comparative Examples

[0147] Examples 1-7

[0148] Prepare a 20 mL impregnation solution by mixing an active metal precursor (copper nitrate for Cu, cobalt nitrate for Co, nickel nitrate for Ni, ferric nitrate for Fe, and molybdenum nitrate for Mo) with hydrochloric acid (15 wt%) and water, ensuring the pH of the impregnation solution is 3.2. The concentration of the impregnation solution is selected according to the catalyst formulation. Take 20 g of support and slowly add the impregnation solution to the support while stirring to ensure uniform loading of the impregnation solution onto the support. The impregnation temperature is 25 °C. After impregnation, the support is dried under nitrogen purging at 120 °C for 3 h, and then calcined in air at 600 °C for 4 h. The catalyst formulation and properties are shown in Table 2, where the support is calculated on a dry basis (calcined at 800 °C for 1 h), and the active metal is calculated as a metal oxide.

[0149] Comparative Examples 1-5

[0150] Prepare a 20 mL impregnation solution by mixing an active metal precursor (copper nitrate for Cu, cobalt nitrate for Co, nickel nitrate for Ni, ferric nitrate for Fe, and molybdenum nitrate for Mo) with hydrochloric acid (15 wt%) and water, ensuring the pH of the impregnation solution is 3.2. The concentration of the impregnation solution is selected according to the catalyst formulation. Take 20 g of support and slowly add the impregnation solution to the support while stirring to ensure uniform loading of the impregnation solution onto the support. The impregnation temperature is 25 °C. After impregnation, the support is dried under nitrogen purging at 120 °C for 3 h, and then calcined in air at 600 °C for 4 h. The catalyst formulation and properties are shown in Table 2, where the support is calculated on a dry basis (calcined at 800 °C for 1 h), and the active metal is calculated as a metal oxide.

[0151] Comparative Example 6

[0152] The method is the same as in Example 1, except that Ni is used instead of Cu, and nickel nitrate is used as the precursor of Ni. The catalyst formulation and properties are shown in Table 2.

[0153] Table 2 Catalyst formulation and property parameters

[0154]

[0155] Test case

[0156] The catalysts from Examples 1-7 and Comparative Examples 1-6 were evaluated for selective hydrogenation of butadiene and 1-butene isomerization in a fixed-bed reactor. The reactions were carried out in a fixed-bed microreactor (hereinafter referred to as a fixed-bed microreactor). The evaluation conditions were: reaction temperature 225℃, reaction pressure (reactor inlet pressure) 1.5MPa, feed gas flow rate 100mL / min (hydrogen volume fraction 10%, 1,3-butadiene volume fraction 2%, 1-butene volume fraction 20%, n-butane volume fraction 20%, mercaptan content 50ppm, and the remainder being nitrogen), and catalyst loading 5g. Before evaluation, the catalyst was reduced under the following conditions: reducing atmosphere of 10% hydrogen by volume, inert gas of 90% nitrogen by volume, reduction temperature of 400℃, and reduction time of 2h. The evaluation results are shown in Table 3.

[0157] in,

[0158]

[0159]

[0160] Table 3

[0161]

[0162] As shown in Table 3, the non-precious metal hydrogenation catalyst provided by the present invention has higher conversion activity than the butadiene selective hydrogenation and 1-butene isomerization catalysts prepared by existing methods. Under the same active metal conditions, it can have higher butadiene selectivity and butene skeleton isomerization activity, and is especially suitable for processing sulfur-containing feedstocks.

[0163] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

[0164] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A non-precious metal hydrogenation catalyst, characterized in that, The catalyst comprises an active metal and a support, wherein the support comprises alumina, a molecular sieve having a BEA structure, and a modified metal oxide, wherein the modified metal oxide is at least one selected from titanium oxide, zirconium oxide, and cerium oxide; wherein the modified metal oxide has η < 0.3 and θ ≥ 50, where η = weight percentage of crystalline phase modified metal oxide in the support / weight percentage of chemical composition of modified metal oxide in the support, and θ = weight percentage of modified metal oxide on the surface of the support / weight percentage of chemical composition of modified metal oxide in the support, and titanium oxide is calculated as TiO2, cerium oxide as CeO2, and zirconium oxide as ZrO2; wherein the active metal comprises Cu and other metal components; wherein the other metal components are at least one selected from Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca, and W; Based on the total amount of carrier, the content of alumina is 50-90% by weight, the content of molecular sieve with BEA structure is 2-40% by weight, and the content of modified metal oxide is 1-40% by weight. Based on the total amount of catalyst, the Cu content, calculated as CuO, is 5-30% by weight, and the content of other metal components, calculated as oxides, is 3-20% by weight.

2. The catalyst according to claim 1, wherein, Based on the total amount of catalyst, the content of the active metal is 5-40% by weight, and the content of the support is 60-95% by weight.

3. The catalyst according to claim 2, wherein, Based on the total amount of catalyst, the content of the active metal is 10-35% by weight, and the content of the support is 65-90% by weight.

4. The catalyst according to claim 1, wherein, In the catalyst, based on the total amount of catalyst, the Cu content (calculated as CuO) is 5-25% by weight, and the content of other metal components (calculated as oxides) is 5-15% by weight.

5. The catalyst according to claim 1 or 2, wherein, The other metal components are selected from at least one of Ni, Fe, Mo and Co.

6. The catalyst according to claim 1, wherein, The alumina content is 60-80% by weight, the molecular sieve with BEA structure content is 10-30% by weight, and the modified metal oxide content is 2-15% by weight.

7. The catalyst according to claim 1, wherein, The modified metal oxide is titanium oxide, with the content of titanium oxide (calculated as TiO2) being 2-20% by weight, zirconium oxide (calculated as ZrO2) being 0-8% by weight, and cerium oxide (calculated as CeO2) being 0-8% by weight, based on the total amount of the carrier.

8. The catalyst according to claim 1, wherein, The catalyst has a phase structure of at least one of γ-alumina, η-alumina, p-alumina and χ-alumina.

9. The catalyst according to claim 1, wherein, The molecular sieve with the BEA structure is selected from at least one of hydrogen-type β-zeolite molecular sieves, phosphorus-containing β-zeolite molecular sieves, rare earth metal-containing β-zeolite molecular sieves, and β-zeolite molecular sieves containing both phosphorus and rare earth metals.

10. The catalyst according to claim 1, wherein, The modified metal oxide has an η of 0 and an θ of 50-95.

11. The catalyst according to claim 1, wherein, In the catalyst, the ratio of Brønsted acid to Lewis acid in the support is not less than 0.

5.

12. The catalyst according to claim 1, wherein, In the catalyst, the ratio of Brønsted acid to Lewis acid in the support is 0.5-5.

13. The catalyst according to claim 1, wherein, The catalyst has a specific surface area of ​​100-450 m². 2 / g, with a pore volume of 0.3-2.0 mL / g.

14. The catalyst according to claim 13, wherein, The catalyst has a specific surface area of ​​120-350 m². 2 / g, pore volume is 0.5-1.2mL / g.

15. The method for preparing the non-precious metal hydrogenation catalyst according to claim 1, wherein, The method includes the following steps: (1) Alumina, molecular sieve with BEA structure, water and acid solution are brought into contact to form a slurry; the slurry is then successively shaped, dried and calcined to form a mixed matrix carrier; (2) The mixed matrix carrier obtained in step (1) is brought into contact with the gas-carried modified metal oxide precursor gas flow to obtain a mixed matrix loaded with modified metal oxide precursor. (3) Hydrolyze the mixed matrix of the loaded modified metal oxide precursor, calcine it, and obtain the support; (4) The support is impregnated with an active metal precursor solution to obtain a support containing an active metal precursor; the active metal includes Cu and other metal components; wherein the other metal components are at least one of Sn, Ni, Fe, Ag, In, Re, Mo, Co, Ca and W; (5) Dry and calcine the carrier containing the active metal precursor; The modified metal oxide is at least one of titanium oxide, zirconium oxide, and cerium oxide.

16. The preparation method according to claim 15, wherein, The amounts of alumina, BEA-structured molecular sieve, modified metal oxide, and active metal used in the catalyst are such that, based on the total amount of catalyst, the content of the active metal is 5-40% by weight, and the content of the support is 60-95% by weight.

17. The preparation method according to claim 15, wherein, Based on the total amount of catalyst, the content of the active metal is 10-35% by weight, and the content of the support is 65-90% by weight.

18. The preparation method according to claim 15, wherein, In the catalyst, based on the total amount of catalyst, the Cu content (calculated as CuO) is 5-30% by weight, and the content of other metal components (calculated as oxides) is 3-20% by weight.

19. The preparation method according to claim 18, wherein, In the catalyst, based on the total amount of catalyst, the Cu content (calculated as CuO) is 5-25% by weight, and the content of other metal components (calculated as oxides) is 5-15% by weight.

20. The preparation method according to claim 15, wherein, The other metal group is selected from at least one of Ni, Fe, Mo and Co.

21. The preparation method according to claim 15, wherein, In step (1), the alumina is selected from at least one of γ-alumina, η-alumina, p-alumina, χ-alumina and hydrated alumina.

22. The preparation method according to claim 15, wherein, In step (1), the specific surface area of ​​the alumina is 100-300 m². 2 / g, with a pore volume of 0.3-2.0 mL / g.

23. The preparation method according to claim 22, wherein, In step (1), the specific surface area of ​​the alumina is 120-250 m². 2 / g, pore volume is 0.8-1.8mL / g.

24. The preparation method according to claim 15, wherein, In step (1), the molecular sieve with the BEA structure is selected from at least one of hydrogen-type β-zeolite molecular sieve, phosphorus-containing β-zeolite molecular sieve, rare earth metal-containing β-zeolite molecular sieve, and β-zeolite molecular sieve containing phosphorus and rare earth metal.

25. The preparation method according to claim 15, wherein, In step (1), the acid solution is selected from water-soluble inorganic acids and / or organic acids.

26. The preparation method according to claim 25, wherein, In step (1), the acid solution is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid and acetic acid.

27. The preparation method according to claim 15, wherein, In step (1), the amount of acid solution used is such that the pH value of the slurry is 1-5.

28. The preparation method according to claim 27, wherein, In step (1), the amount of acid solution used is such that the pH value of the slurry is 1.5-4.

29. The preparation method according to claim 15, wherein, In step (1), the specific surface area of ​​the mixed matrix carrier is not less than 150 m². 2 / g.

30. The preparation method according to claim 15, wherein, In step (1), the specific surface area of ​​the mixed matrix carrier is 150-500 m². 2 / g.

31. The preparation method according to claim 30, wherein, In step (1), the specific surface area of ​​the mixed matrix carrier is 200-400 m². 2 / g.

32. The preparation method according to claim 15, wherein, In step (1), the pore volume of the mixed matrix carrier is not less than 0.3 mL / g.

33. The preparation method according to claim 32, wherein, In step (1), the pore volume of the mixed matrix carrier is 0.3-2 mL / g.

34. The preparation method according to claim 33, wherein, In step (1), the pore volume of the mixed matrix carrier is 0.5-1.5 mL / g.

35. The preparation method according to claim 15, wherein, In step (1), the drying conditions are: temperature of 50-250℃ and time of 0.5-5h; the calcination conditions are: temperature of 400-700℃ and time of 1-12h.

36. The preparation method according to claim 15, wherein, In step (2), the modified metal oxide precursor is at least one of titanium oxide precursor, zirconium oxide precursor and cerium oxide precursor.

37. The preparation method according to claim 36, wherein, In step (2), the titanium oxide precursor is selected from at least one of titanium tetrachloride, ethyl titanate, tetrabutyl titanate, isopropyl titanate, and titanium acetate; the zirconium oxide precursor is selected from at least one of zirconium tetrachloride, zirconium ethoxide, zirconium methoxide, zirconium isopropoxide, and tetrabutyl zirconate; and the cerium oxide precursor is selected from at least one of cerium trichloride, cerium ethoxide, and cerium isopropoxide.

38. The preparation method according to claim 15, wherein, In step (2), the modified metal oxide is titanium oxide, and the content of titanium oxide, calculated as TiO2, is 2-20% by weight, based on the total amount of the carrier.

39. The preparation method according to claim 15, wherein, In step (2), the content of titanium oxide, calculated as TiO2, is 5-15% by weight, based on the total amount of the carrier.

40. The preparation method according to claim 15, wherein, In step (2), the gas is an anhydrous inactive gas, and the water content in the anhydrous inactive gas does not exceed 10 ppm.

41. The preparation method according to claim 15, wherein, In step (2), the content of modified metal oxide precursor in the gas stream carrying the modified metal oxide precursor is 0.1-5 g / L, wherein the content of modified metal oxide precursor is calculated as metal oxide.

42. The preparation method according to claim 15, wherein, In step (2), the gas temperature is room temperature - 350°C, the contact temperature is 15-350°C, and the contact pressure is 0.1-10 atm.

43. The preparation method according to claim 15, wherein, In step (2), the ratio of the volumetric flow rate of the gas per minute to the volume of the mixed matrix carrier is 10-80:1; wherein the volume of the gas is measured in terms of volume under standard conditions, and the volume of the mixed matrix carrier is measured in terms of bulk volume; in step (2), the mixed matrix carrier is in contact with the gas flow of the modified metal oxide precursor carried by the gas in a fluidized state, or in contact with the gas flow under stirring; the fluidized state is a bubbling bed, a turbulent bed, a fast bed, or a conveying bed.

44. The preparation method according to claim 43, wherein, In step (2), the ratio of the gas volume flow rate per minute to the volume of the mixed matrix carrier is 20-60:1; wherein the gas volume is measured in terms of volume under standard conditions, and the mixed matrix carrier volume is measured in terms of bulk volume.

45. The preparation method according to claim 15, wherein, In step (3), the mixed matrix of the modified metal oxide precursor is prepared by hydrolysis as follows: the mixed matrix of the modified metal oxide precursor is contacted with a gas containing water vapor, wherein the ratio of the gas containing water vapor to the mixed matrix is ​​3-50:1, the ratio being the ratio of the volume of the gas containing water vapor to the volume of the mixed matrix under standard conditions, wherein the proportion of water vapor in the gas containing water vapor to the total volume of the gas is 0.1-100% by volume, and the other gases in the gas containing water vapor are at least one of inert gas, nitrogen and air.

46. ​​The preparation method according to claim 45, wherein, In step (3), the ratio of the water vapor-containing gas to the mixed matrix is ​​10-30:1, where the ratio is the ratio of the water vapor-containing gas to the mixed matrix volume under standard conditions, and the proportion of water vapor in the total gas volume is 3-100%.

47. The preparation method according to claim 15, wherein, In step (3), the hydrolysis time is 1-50h.

48. The preparation method according to claim 47, wherein, In step (3), the hydrolysis time is 2-30 hours.

49. The preparation method according to claim 15, wherein, In step (3), the roasting temperature is 400-700℃ and the roasting time is 1-12h.

50. The preparation method according to claim 15, wherein, In step (4), the pH of the solution containing Cu and other metal precursor active metals is 2-4.

51. The preparation method according to claim 15, wherein, In step (4), the immersion temperature is 10-150℃ and the time is 1-24h.

52. The preparation method according to claim 15, wherein, In step (5), the drying temperature is 50-250℃ and the time is 1-24h.

53. The preparation method according to claim 15, wherein, In step (5), the roasting temperature is 400-700℃ and the roasting time is 2-12h.

54. The application of the non-precious metal hydrogenation catalyst according to any one of claims 1-14 in the selective hydrogenation of butadiene and the isomerization reaction of 1-butene.

55. A method for selective hydrogenation of butadiene and isomerization of 1-butene, wherein, This includes contacting a butadiene-containing feedstock with a non-precious metal catalyst as described in any one of claims 1-14 to carry out a hydrogenation reaction.

56. The method according to claim 55, wherein, The contact conditions include: a reaction temperature of 100-350℃, a pressure of 0.05-3MPa, and a weight hourly space velocity of 0.5-50h⁻¹. -1 .

57. The method of claim 55, wherein, The butadiene-containing feedstock is C4 by-product from sulfur-containing FCC in a refinery or C4 raffinate from ethylene cracking.

58. The method according to claim 55, wherein, The butadiene-containing feedstock is a hydrogen-containing stream, with the following volume fractions: hydrogen gas fraction 1-10%, 1,3-butadiene volume fraction 1-5%, 1-butene volume fraction 15-30%, n-butane volume fraction 15-30%, other gases serving as carrier gases, and thiol content 10-200 ppm.

Citation Information

Patent Citations

  • Fine desulfurize method for carbon four components of refinery

    CN101249366A

  • Fine desulfurization method of C4 fraction

    CN103102987A

  • Thioetherification processes for the removal of mercaptans from gas streams

    TW201011100A

  • Hydrocarbon oil desulfurization catalyst containing FAU-structure and / or BEA-structure molecular sieve, preparation method of hydrocarbon oil desulfurization catalyst and process for hydrocarbon oil desulfurization

    CN109718830A